NEUROFIBROMATOSIS TYPE 1 OR GIANT MELANOCYTIC NEVUS: PROBLEMS OF DIAGNOSTIC - A. S. Ol’shanskaya; A. V. Dyuzhakova; I. P. Artyukhov; N. A. Shnayder; D. V. Dmitrenko; Yu. V. Karacheva (Русский журнал детской неврологии)
Neurofibromatosis type 1 (NF-1) is a hereditary disease mainly affecting skin and peripheral nervous system. Individual signs of cutaneous manifestations of NF-1 can imitate or be combined with other neurocutaneous syndromes. At present on the outpatient phase is not always possible to conduct a detailed examination of the patients with NF-1 and to determine the indications for modern diagnostic examination in a specialized hospital. It can be important to verify the diagnosis. The authors presented short review of russian and foreign literature and clinical case of the patient with a specific lesion of the skin against the background of congenital giant melanocytic nevus. Problems of differential diagnosis of NF-1 and congenital giant pigmented nevus were analyzed.